1991
DOI: 10.1177/095646249100200511
|View full text |Cite
|
Sign up to set email alerts
|

Is Bacterial Vaginosis a Sexually Transmitted Disease?

Abstract: The sexual behaviour of 400 women with and 400 women without bacterial vaginosis from a health screening programme was investigated by a questionnaire to see if women with bacterial vaginosis had similar behaviours to women considered at risk for STDs. These patients were randomly selected from computer records. Eight hundred questionnaires were distributed and 641 women answered. The age of first sexual intercourse was lower among women with bacterial vaginosis (17.8 years) than those without (18.6 years; P l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 8 publications
3
27
0
Order By: Relevance
“…13 Previous studies have reported that the prevalence of BV also rises with the number of lifetime sexual partners and is more common in those with a lower age of first intercourse. 18 In this study the risk of BV was greatest among those reporting more than one partner in the past 3 months reflecting the pattern reported for the known STIs, gonorrhoea, and Chlamydia trachomatis. This suggests that a diagnosis of BV is associated with a recent partner change.…”
Section: Discussionsupporting
confidence: 72%
“…13 Previous studies have reported that the prevalence of BV also rises with the number of lifetime sexual partners and is more common in those with a lower age of first intercourse. 18 In this study the risk of BV was greatest among those reporting more than one partner in the past 3 months reflecting the pattern reported for the known STIs, gonorrhoea, and Chlamydia trachomatis. This suggests that a diagnosis of BV is associated with a recent partner change.…”
Section: Discussionsupporting
confidence: 72%
“…BV is a syndrome associated with adverse pregnancy outcomes, which is not exclusively considered an STD but which has been demonstrated to be transmitted sexually [44]. BV is characterized by a disturbance of the normal vaginal flora, with a loss of H 2 O 2 -producing Lactobacillus species and an increase in the numbers of gram-variable coccobacilli (Gardnerella vaginalis and Bacteroides spp.…”
Section: Bacterial Vaginosismentioning
confidence: 98%
“…In nonpregnant women [39], BV increases risk of posthysterectomy infections [40,41] and PID [32,42], and risk of acquiring N. gonorrhoeae [8,43,44]. Finally, BV itself may cause endocervical inflammation that manifests as mucopurulent cervicitis [45,46].…”
Section: Introductionmentioning
confidence: 94%